1972
DOI: 10.1037/h0032477
|View full text |Cite
|
Sign up to set email alerts
|

Implicit associative responses in verbal discrimination acquisition.

Abstract: Predictions from the frequency theory of verbal discrimination learning for interitem manipulations of implicit associative responses were examined in four experiments varying methodological factors. In general, the predictions with respect to lists involving associatively related right items were supported only when 5s were explicitly instructed regarding the associative relationships. In lists involving associatively related wrong items, the predicted inferiority relative to the control condition was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Although Ekstrand et al (1966) reported significant facilitation for the interitem-AR condition, consistent with the frequency theory , a series of six experiments (Kanak , Cole, & Thornton, 1970;Kanak, Cole, & Eckert, 1972) reproduced this finding in only one experiment, and only then when Ss were instructed regarding the associative relationship , despite the manipulation of a number of potentially pertinent methodological variables. Similarly, the dominance or associative strength of the relationship between related R items failed to be defined as a significant variable (Mueller, Kanak, & Flannagan , in press) in an interitem-AR manipulation, in contrast to a successful similar manipulation (though within a mixed list) in the intrapair condition (McCarthy, 1973).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Although Ekstrand et al (1966) reported significant facilitation for the interitem-AR condition, consistent with the frequency theory , a series of six experiments (Kanak , Cole, & Thornton, 1970;Kanak, Cole, & Eckert, 1972) reproduced this finding in only one experiment, and only then when Ss were instructed regarding the associative relationship , despite the manipulation of a number of potentially pertinent methodological variables. Similarly, the dominance or associative strength of the relationship between related R items failed to be defined as a significant variable (Mueller, Kanak, & Flannagan , in press) in an interitem-AR manipulation, in contrast to a successful similar manipulation (though within a mixed list) in the intrapair condition (McCarthy, 1973).…”
mentioning
confidence: 55%
“…It is therefore puzzling that its operation has not been more consistently demonstrated in the interitem-AR condition. Kanak et al (1972) pointed out that the interpair and intrapair manipulations involve a contrast of function (i.e., W or R) of the associatively related items which may serve as a sufficient cue to activate attention to the associative relationship even in unmixed lists. The fact that Eberlein and Raskin (1968) found comparable interference for the interpair condition without and with instructions regarding the list composition is consistent with this notion.…”
mentioning
confidence: 99%
“…Kanak & Jones, 1974) reported in the literature has this result been replicated, and only then when the subjects were instructed regarding the associative relationship (Kanak, Cole, & Eckert, 1972;Experiment II).…”
mentioning
confidence: 75%
“…Thus the lack of consistent evidence for its operation in the interitem-AR condition is paradoxical. Kanak et al (1972) pointed out that the interpair and intrapair manipulations both involve a contrast of item function (i.e., W or R) of the associatively related items which may activate awareness of and attention to the presence of associations even in unmixed lists. In an unmixed list interitem-AR condition, however, as Kanak and Jones have noted, such an item-function contrast cue is not present to provide the same cue for the subjects to attend to the associative relationship.…”
mentioning
confidence: 99%
“…These contradictory fi ndings challenged investigators for decades. For details see Izawa (1972Izawa ( , 1974Izawa ( , 1977, Izawa, Hayden, and Isham (1980), and Kanak, Cole, and Eckert (1972).…”
mentioning
confidence: 99%